Caracterización de los productos forestales no maderables de origen vegetal, en cuatro comunidades de la parroquia Guanazán, cantón Zaruma, provincia de El Oro - Morán Peñaloza, María Alejandra (2020)
Non-Timber Forest Products (NTFPs) are part of the life of Ecuadorian rural sectors, however, their ignorance is a problem for the conservation of the ecosystems of the Guanazán parish, of the Zaruma canton, for which this research was carried out to generate information on the species that have NWFPs, and guidelines for their management and sustainable use were developed. The information was compiled by applying 200 structured surveys to the inhabitants of four communities of the parish; 54 in Huartiguro, 53 in downtown Guanazán, 43 in La Cruz and 50 in Cochaguro; made to men and women by age groups, where 71 species of trees, shrubs and herbs comprised of 69 genera and 46 families were recorded. 43 species with the highest frequency of uses for human medicine were recorded. The species that presented the highest use value are: Alnus acuminata Kunth, Acacia melanoxylon R. Br. Regarding the level of significant use (NUS), of the 71 species registered in the study, no achievement had a value greater than 20% , but for interpretation purposes the following species were considered: Alnus acuminata Kunth, Macleania rupestris (Kunth) ACSm., Juglans neotropica Diels, these species were considered to have a higher number of use citations. To evaluate the results of value of use, frequency of use and level of significant use, the SWOT matrix was used and based on the knowledge of the population about the use of the species, management programs and use of NWFP were developed, in order to to rescue the traditional and cultural knowledge of the families of the Guanazán parish. Keywords: Ethnobotany, perception of the local population, NTFP, Guanazán.